Nutrient Content of Corn Straw (Crude Fibre, Crude Fat and TDN) Caused by Different Doses of Urea - Noersidiq, Azhary; Yanuarianto, Oscar; Fahrullah, Fahrullah; Maslami, Vebera; Hasma, Hasma (Jurnal Pijar Mipa, 2024)
This research aims to evaluate ammoniated corn straw's nutritional content and determine the best urea dose. Corn straw is one of the alternative feed sources from waste in the livestock industry. They contain crude 6.38%protein, 30.19%crude fibre, 2.81%crude fat, 51.69% EMWN, 8.94%ash, 53.12%TDN, 22.5% hemicellulose, 10.6% lignin, and 32.9% cellulose. However, the nutritional quality of corn straw can be affected by various factors, such as the high lignin content. It can bind to cellulose and hemicellulose, reducing digestibility and utilization as animal feed, so it needs to be processed first, one of which is ammoniation technology using urea. This research used 500 grams of corn straw and urea for the ammoniation process based on dry matter (DM) of corn straw for urea doses. The research designed by a complete randomized design (CRD) consisting of 4 treatments and 4 replications, namely T1= only corn straw (control), T2= corn straw with 2% urea, T3= corn straw with 4% urea and T4= corn straw with 6% urea. The variables measured were crude fiber, crude fat,, and TDN. The results showed that urea used in the ammoniation process of corn straw showed a significant effect (P<0.05) on increasing the content of crude fiber, crude fat,, and TDN. Urea can stretch the bonds between ligncellulose, It was concluded that the best urea dose is at 6%, with 25.91% crude fibre, 2.65% crude fat, and 60.91% TDN respectively.